BEHIND THE DEVELOPMENT MAP: THE PERFORMANCE OF BAPPEDA EMPLOYEES DETERMINES THE DIRECTION IN STRUCTURAL ANALYSIS PERSPECTIVE - Devi Ria Amalinda; Vera Firdaus; Detak Prapanca; Rezza Dwi Amalia (International Journal of Economic Integration and Regional Competitiveness, 2026)
Objective: This study aims to examine the influence of considerate leadership and compensation on employee performance through the mediation of job satisfaction at BAPPEDA Sidoarjo. Method: This type of research uses a quantitative descriptive method. The location of the research conducted by the author to test the hypothesis is at BAPPEDA Sidoarjo which is located at Jl. Sultan Agung No.13, Gajah Timur, Magersari. Sidoarjo District, Sidoarjo Regency, East Java, with a postal code of 61212. The number of respondents in this study was 60 employees. This study uses primary data from questionnaires with a Likert scale processed using SmartPLS with validity tests and reliability tests. Results: The results obtained are: 1) Considerate leadership has a positive and significant effect on employee performance and job satisfaction at the Sidoarjo Regency Regional Development Planning Agency (BAPPEDA); 2) Compensation has a positive and significant effect on employee performance and job satisfaction at the Sidoarjo Regency Regional Development Planning Agency (BAPPEDA). 3) Job satisfaction has a positive and significant influence on employee performance at the Sidoarjo Regency Regional Development Planning Agency (BAPPEDA). Novelty: The novelty of this research lies in its empirical focus on testing the mediating role of job satisfaction between considerate leadership, compensation, and employee performance specifically within the context of a local government agency (BAPPEDA Sidoarjo) using PLS-SEM analysis.